A 1999 Social Accounting Matrix (SAM) For Uganda - International Food Policy Research Institute (International Food Policy Research Institute, 2005)
The 1999 Social Accounting Matrix (SAM) for Uganda was constructed to meet the economywide modeling requirements undertaken by the International Food Policy Research Institute (IFPRI) "Strategic Criteria for Rural Investments in Productivity (SCRIP)" project. The SAM has a detailed treatment of the agriculture sector, in terms of both disaggregation by crop and by region (six agro-climatic zones). In addition, the SAM distinguishes between consumption out of own production by households (about 11 percent of total household expenditures in 1999) and marketed consumption. Furthermore, the SAM explicitly accounts for transactions costs (also referred to as marketing margins) associated with domestic, import, and export marketing.